Geothermal Country Update for Peru, 2010-2014 - Cruz Pauccara, Vicentina (2015)
Peru is one of the countries in South America with greatest geothermal potential because it is located within the Pacific Ring of Fire, where the subduction process occurs between the Nazca and South American Plates. This is the key factor in the formation of the Andes Cordillera (Andean Mountain Range) located in the southern part of Peru, where many active volcanoes can be found. Consequently, the magmatic and tectonic processes have allowed the development of geothermal environments in this region. The evaluation of the Peruvian geothermal potential begun in the 70´s where most of the studies were undertaken by government institutions, with some technical assistance from countries that have developed geothermal activities. Six geothermal regions have been identified in Peru. The most promising of these is the region 5, also called “Eje Volcánico Sur”, where all the actives volcanoes are located. Whereas, the other five regions have good potential for low and moderate enthalpy resources. Historically Peru has developed activities in the direct uses of the geothermal resources, mainly in balneology, where some hot springs have been used since the Inca´s Empire. Since 2007, Peru has been receiving economical and technical assistance to start the development of geothermal energy. It was in this year that the Japanese government supported the pre-feasibility studies in two of the most promising geothermal fields in the country, Calientes and Borateras, where 150 MWe were estimated to be found. In 2010, the Japanese government also elaborated “The Master Plan for Development of Geothermal Energy in Peru” where they studied 15 geothermal fields and 3,000 MWe was the first estimated of the geothermal potential of the country. Peru, is one of the two South American countries (the other is Chile), that has geothermal legislation. The Geothermal Law in Peru was published in 1997 and its newest By-laws were published in 2010. As a result, many geothermal companies have looked into investing in Peru as a good opportunity to develop the geothermal resources. There are many private companies exploring geothermal resources currently in Peru. The government has granted more than 30 authorizations areas, most of them located in southern Peru. However, until now no electricity from geothermal resources has been produced and there have not been any drilling for production wells done in the country.